Evaluating the effectiveness of Autologous Conditioned Serum (ACS) & Platelet-Rich Plasma (PRP) in Early Osteoarthrosis of Knee - K. Satya Kumar (New Horizons in Medicine and Medical Research Vol. 12, 2022)
The objective of this study is to evaluate the Effectiveness of Platelet Rich Plasma and Autologous Conditioned Serum in Decreasing Pain, Stiffness, and Improving Function in Patients with Early Osteoarthrosis Knee. Osteoarthrosis is a failure of the synovial-lined diarthrodial joint. Knee osteoarthrosis is the most common cause of chronic impairment in the elderly. Because of the extended life expectancy of the Indian population, the prevalence of osteoarthrosis is increasing. A volume of plasma with a platelet concentration higher than that of the peripheral blood is known as platelet rich plasma (Prp). Prp’s efficacy in improving musculoskeletal diseases, including osteoarthrosis, has been shown in several fundamental, preclinical, and even clinical case investigations and trials. autologous conditioned serum (Acs) is an autologous blood product enriched with interleukin-1 receptor antagonist (il-1ra), a naturally occurring inhibitor of interleukin-1 (il-1). Our research on acs and platelet-rich plasma has revealed an interesting new therapy option for knee osteoarthrosis, and it has proven effective during a two-year observation period.